ICS/LABA Combined With Subcutaneous Immunotherapy Modulates the Th17/Treg Imbalance in Asthmatic Children - Dai, Huan; Zheng, Rongying; Wang, Like; Wan, Jinyi; Tong, Yu; Zhao, Wei; Zhang, Weixi (Frontiers in Immunology, 2022)
Rationale: The imbalance of T helper (Th17) cell and regular T (Treg) cell are involved in allergic asthma pathogenesis. We hypothesized that ICS/LABA could modulate the Th17/Treg imbalance and that subcutaneous immunotherapy (SCIT) could coordinate with ICS/LABA to rebalance the dysfunction of Th17/Treg. Methods: Thirty house dust mites (HDM) allergic asthmatic children and fifteen healthy control subjects were enrolled in this study. Fifteen asthmatic children were treated by ICS/LABA powder inhalation, while the other fifteen asthmatic children were treated by ICS/LABA powder inhalation combined with HDM-SCIT. Asthmatic subjects were followed up for 6 months, but 2 asthmatics treated with ICS/LABA were lost to follow-up. Flow cytometry was used to determine the proportions of Th17 and Treg in CD4+ T cells from peripheral blood mononuclear cells (PBMCs). Serum levels of IL-17A and IL-10 were assessed by ELISA. Result: ICS/LABA treatment significantly reduced the percentage of Th17 cells (1.252±0.134% vs. 2.567±0.386%), serum IL-17A (49.42±2.643 pg/ml vs. 66.75±3.442 pg/ml) and Th17/Treg ratio (0.194±0.025 vs. 0.439±0.072) compared to baseline (P＜0.01). The ICS/LABA+HDM-SCIT treatment group showed similar reduction in the percentage of Th17 cells (1.11±0.114% vs. 2.654±0.276%), serum IL-17A (49.23±2.131 pg/ml vs. 66.41±2.616 pg/ml) and the Th17/Treg ratio (0.133±0.015 vs. 0.4193±0.050) (P＜0.01). ICS/LABA+HDM-SCIT treatment group demonstrated elevated Treg percentages (8.483±0.408% vs. 6.549±0.299%) and serum IL-10 levels (127.4±4.423 pg/ml vs. 93.15±4.046 pg/ml), resulting in a lower Th17/Treg ratio than the ICS/LABA group. Conclusion: ICS/LABA treatment regulates Th17/Treg imbalance mainly by mitigating Th17-induced inflammation in asthma patients. The addition of SCIT further enhanced such effect by upregulating Treg cells.